Estimating the Effect of Working from Home on Parents' Division of Childcare and Housework: A New Panel IV Approach - Simone Schüller (Institute of Labor Economics (IZA), 2025)
This study investigates whether (and how) working from home (WFH) affects the gender division of parental unpaid labor. I use the recent COVID-19 pandemic that brought an unanticipated yet lasting shift to WFH combined with a measure of occupational WFH feasibility (Alipour et al. 2023) as a quasi-experiment to employ an instrumental variable (IV) approach and estimate causal effects. I use unique longitudinal data from the "Growing up in Germany" ( AID:A) panel study, which administered a prepandemic wave in 2019, and a post-pandemic wave in 2023. AID:A contains rich information on mothers' and fathers' time use for work, commuting, childcare, and housework. I find that the most robust effects emerge for paternal WFH intensity (at least weekly WFH) on parental division of housework: families in which fathers start weekly WFH in the period 2019 to 2023—due to their occupational WFH capacity in combination with the pandemic WFH-boost—experience a significant decrease in the maternal share of parental housework. Interestingly, this shift appears to be mainly driven by a reduction of maternal time use for housework (combined with an increase of her work hours) and less by an increase in paternal time use for housework suggesting crossparent effects of WFH.
Keywords: D13; I31; J13; 330; COVID-19; gender equality; time use; housework; childcare; working from home; AID:A panel survey